Office organization and method - Mills, Geoffrey; Standingford O. (London Sir Isaac Pitman and sons, 1963)
This book showcase recent developments in office practice and in office machines, with emphasis more on what the office worker has to achieve while performing office duties.
Includes bibliographical reference and index
eej 15/01/2019, ijb 10/04/2019
Loans
Keywords: Office management; Office equipment and supplies; Office practice